CHANGES IN CONSUMER BEHAVIOR IN THE MICROECONOMY IN THE DIGITAL AGE: A SYSTEMATIC LITERATURE REVIEW ON THE IMPACT OF E-COMMERCE PLATFORMS, SOCIAL COMMERCE, AND ARTIFICIAL INTELLIGENCE - Vinuzia, Mala; Iswanto, Dedy; Ramayanto, Ramayanto (TECHNOBIZ : International Journal of Business, 2026)
Rapid advancements in digital technology have driven significant transformations in consumer behavior across various economic sectors. This study aims to conduct a systematic synthesis to identify patterns, trends, and implications of changes in consumer behavior within the microeconomy in the digital age. The methodology employed is qualitative, utilizing a Systematic Literature Review (SLR) approach to articles from DOAJ, Scopus, and Google Scholar spanning the period 2016–2025. The results indicate that digital transformation through machine learning and Artificial Intelligence enhances efficiency, personalization, and user experience. Psychological factors such as perceived usefulness, perceived risk, and consumer engagement also influence consumer decisions. Additionally, social commerce and the dominance of Generation Z reinforce interactive consumption patterns. These findings confirm that consumer behavior is multidimensional and influenced by the interplay of technology, psychology, and the digital ecosystem.